First record of the genera Centistoides van Achterberg and Pygostolus Haliday (Hymenoptera: Braconidae) in Brazil, with the description of new species - Almeida, Luis Felipe Ventura De; Penteado-Dias, Angélica Maria (Zootaxa, 2018)
The genera Centistoides and Pygostolus are recorded for the first time in Brazil. Centistoides manoeli sp. nov., Pygostolus carolinae sp. nov. and Pygostolus odeterochae sp. nov. are described and illustrated.